Gambaran Status Anemisa Masyarakat Kelurahan Rahandouna Kecamatan Poasia Kota Kendari - Irma Yunawati; Wa Ode Salma; Nurnashriana Jufri; Alifia Nur Rabiahni; Sri Kaltsum Fadilat. AR; Iken Wulandari; Naufalia Mardiati; Tetih Yanuliah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anemia is a medical condition characterized by a low number of red blood cells or low hemoglobin levels in the blood, namely <12 mg/dl for women and <13 mg/dl for men, thereby reducing the capacity of the blood to carry oxygen to the body's tissues which can cause fatigue. and decreased physical endurance which affects daily activities. This study aims to determine the description of the anemia status of the community in Rahandouna sub-district, Poasia sub-district, Kendari city. The research design used is descriptive, using a cross-sectional approach. The sample in this study was 50 respondents with an age range of 15 to 50 years. The tool used in this study was easy touch to measure the hemoglobin levels of respondents which are an indicator of anemia. The results showed that respondents with low hemoglobin levels reached 14% and the rest were in the normal category. From the results of this study, it was concluded that the problem of anemia in this area was not significant enough.